A medium-high-entropy alloy getter target material and a getter film and a preparation method thereof
Patent Information
- Application Number
- CN202511201557.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-26
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-08-26
AI Technical Summary
[0008]本发明的主要目的在于解决现有技术中吸气性能与力学性能(即吸气薄膜与基体的结合强度)严重矛盾的技术问题
本发明专利利用中高熵合金中浓或多主元素合金,混合熵高等优势,解决目前半导体MEMS传感器件封装材料的吸气性能与力学性能(即吸气薄膜与基体的结合强度)严重矛盾问题。因中高熵合金多元素随机互熔,非周期性排布方式及复杂的势场耦合作用,展现出优异的物理化学特征,具体表现为“四大效应”:即热力学上的高熵效应、结构上的晶格畸变效应、动力学上的迟滞扩散效应和性质上的“鸡尾酒”效应。其“四大效应”在工程应用中,对吸气材料来说,具有很好地提高性能材料吸气性能和力学性能(即吸气薄膜与基体的结合强度)的效果。
Smart Images

Figure CN121023333B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of semiconductor MEMS devices, belonging to IPC C23C 14, and particularly to a medium-high entropy alloy getter target and getter film and its preparation method. Background Technology
[0002] In today's interconnected world, various high-reliability and high-sensitivity semiconductor MEMS sensors have emerged to support the development of AI technology, smart cities, and the Internet of Things. How to enable sensors to achieve the high precision of human senses (sight, hearing, smell, taste, touch, and thought) is a key challenge. Countries are investing heavily in research and development to ensure their leading international position. The high-entropy alloy getter target and getter film developed in this invention are crucial materials for ensuring the high performance and high reliability of various sensors.
[0003] For decades, my country has relied on imports for getter materials used in MEMS semiconductor device packaging (such as those from American company Applied Materials and Italian company SAES). This has become a bottleneck material issue for my country's semiconductor industry chain and high-vacuum device packaging.
[0004] In existing technologies, such as the patent CN108149069A from the Beijing General Research Institute of Nonferrous Metals, the components and their contents, by weight percentage, of the getter alloy material are: zirconium: 33%–65%; titanium: 7%–24%; vanadium: 7%–41%; yttrium: 2%–32%; molybdenum (M): 0%–35%. M is one or a mixture of iron, chromium, manganese, nickel, molybdenum, and aluminum; the sum of the contents of vanadium and M is less than 41%. However, the alloy target in this patent has HCP and BCC phases. Because it is a two-phase structure with different structures and compositions, different sputtering powers are required. When the target is subjected to magnetron sputtering, only one power can be used at a time. This power may be suitable for the HCP phase but not for the BCC phase, or vice versa. Therefore, selective sputtering occurs when fabricating substrate thin films using magnetron sputtering. When the sputtering power is adapted to the HCP phase, the substrate film has a higher HCP content and a lower BCC content; when the sputtering power is adapted to the BCC phase, the substrate film has a higher BCC content and a lower HCP content; the final composition sputtered onto the substrate film is inconsistent with the target composition. Generally, for magnetron sputtering, the ideal target structure is a solid solution phase, meaning one target corresponds to one phase structure. This is because each target, when working in the magnetron sputtering furnace, corresponds to only one sputtering power at the same time. It's impossible for one power source to correspond to two power sources simultaneously. Therefore, the target must be of one phase. This ensures a uniform composition of the sputtered film. If the target has two components, it means that during sputtering, the technician must set the power to only one of the two phases (HCP or BCC phase in Beijing General Research Institute of Nonferrous Metals patent CN108149069A), and the target will selectively sputter during operation. This will cause the composition of the target material transferred onto the thin film to change (only suitable for HCP or only suitable for BCC, because the composition and cell structure of HCP phase BCC are different from those of FCC phase).
[0005] Patent CN118682135A from the Changchun Institute of Applied Chemistry, Chinese Academy of Sciences, provides a titanium-vanadium hydrogen storage alloy block with the following composition: TiV2-xBx, 1.4≥x≥0.6, where the B-side element is one or more elements selected from Mn, Cr, Ni, Zr, Fe, Cu, and Co; or Ti1-yReyV2-xBx, 1.4≥x≥0.6, 0.4≥y≥0.1, where Re is one or more elements selected from La, Ce, Pr, Nd, Sm, and Gd. However, this patented alloy exhibits high brittleness, is easily crushed, and has low mechanical properties such as bonding strength.
[0006] In addition, the applicant and inventor of this invention have also applied for a number of gas-absorbing alloy patents, but none of the gas-absorbing alloy patents are medium-entropy or high-entropy alloys, and their performance degrades significantly when making thin films.
[0007] The reasons for the reliance on imports for medium- and high-entropy alloy getter targets and getter films used in the semiconductor industry chain are as follows: Currently, the getter materials used in semiconductor MEMS sensors exhibit both getter performance and mechanical properties (the bonding strength between the getter film and the substrate, described using a scratch gauge). There is a serious contradiction; the attributes of both cannot be simultaneously considered in the same product. Summary of the Invention
[0008] The main objective of this invention is to solve the technical problem of a severe contradiction between gas-getting performance and mechanical properties (i.e., the bonding strength between the gas-getting film and the substrate) in existing technologies. A medium-high entropy alloy gas-getting target material is provided, wherein the composition of the medium-high entropy alloy gas-getting target material consists of main element A, element C, and element B, wherein the content of main element A is 25-40 at%, the content of element B is 30-45 at%, and the content of element C is 30-45 at %; the formulation equation is: A 25-40 B 30-45 C 30-45 The main element A is selected from one or two of V and Co; the element C is selected from one or two of Fe and RE, where RE is one or more of Pr, Y, Gd, Nd, Er, Sm, and Ce; and the element B is selected from one or two of Ti and Zr.
[0009] The content of the main element A is 25 at%, 26 at%, 27 at%, 28 at%, 29 at%, 30 at%, 31 at%, 32 at%, 33 at%, 34 at%, 35 at%, 36 at%, 37 at%, 38 at%, 39 at%, and 40 at%; the content of element B is 30 at%, 31 at%, 32 at%, 33 at%, 34 at%, 35 at%, 36 at%, 37 at%, 38 at%, 39 at%, 40 at%, 41 at%, 42 at%, 43 at%, 44 at%, and 45 at%; the content of element C is 30 at%, 31 at%, 32 at%, 33 at%, 34 at%, 35 at%, 36 at%, 37 at%, 38 at%, 39 at%, 40 at%, 41 at%, 42 at%, 43 at%, 44 at%, and 45 at%.
[0010] Preferably, the element C is selected from two of Fe and RE, and the RE content in element C is 3-15 at%.
[0011] Further preferably, the RE content in element C is 3-15 at%, and even more preferably, the RE content of rare earth elements in element C is 3 at%, 4 at%, 5 at%, 6 at%, 7 at%, 8 at%, 9 at%, 10 at%, 11 at%, 12 at%, 13 at%, 14 at%, or 15 at%.
[0012] Preferably, the composition of element C is as follows: Fe, Pr, Y; Fe, Pr, Gd; Fe, Pr, Nd; Fe, Pr, Er; Fe, Pr, Sm; Fe, Pr, Ce Fe, Pr, Y, Gd; Fe, Pr, Y, Nd; Fe, Pr, Y, Er; Fe, Pr, Y, Sm; Fe, Pr, Y, Ce; Fe, Pr, Y, Er; Fe, Pr, Y, Er, Sm; Fe, Pr, Y, Er, Ce; Fe, Pr, Y, Gd, Nd, Er, Sm, Ce; Pr, Y, Gd, Nd, Er, Sm, Ce.
[0013] Preferably, the formulation equation for the medium-high entropy alloy getter target is: A 22-50 B 23-50 C 25-40 .
[0014] Specifically, the formulation equation that can be used as a medium-to-high entropy alloy getter target is: V 40 Fe 30 Ti 30 V 40 Fe 27 Ti 30 Pr3, V 40 Fe 20 Ti 20 Zr 10 Pr 10 V 40 Fe 15 Zr 30 Pr 15 V 40 Pr 30 Ti 15 Zr 15 V20 What 20 P. 30 You 15 Zr 15 、What 40 P. 30 You 15 Zr 15 、In 25 Fe 32 You 40 Y3、V 25 Fe 20 You 20 Zr 20 Y 15 、In 25 Fe 20 Zr 40 Y 15 、In 25 Y 35 You 20 Zr 20 、In 15 What 10 Y 35 You 20 Zr 20 、What 25 Y 35 You 20 Zr 20 、In 35 Fe 27 You 35 Gd3、V 35 Fe 20 You 20 Zr 15 Mr. 10 、In 35 Fe 15 Zr 35 Mr. 15 、In 35 Mr. 30 You 20 Zr 15、 In 40 Fe 27 You 30 Nd3、V 40 Fe 20 You 20 Zr 10 No 10 、In 40 Fe 15 Zr 30 No 15 、In 40 No 30 You 15 Zr 15 、In40 Fe 27 Ti 30 Sm3, V 40 Fe 20 Ti 20 Zr 10 Sm 10 V 40 Fe 15 Zr 30 Sm 15 V 40 Sm 30 Ti 15 Zr 15 V 40 Fe 27 Ti 30 Ce3, V 40 Fe 20 Ti 20 Zr 10 Ce 10 V 40 Fe 15 Zr 30 Ce 15 V 40 Ce 30 Ti 15 Zr 15 .
[0015] Specifically, RE can contain multiple components, and the formulation equation for a medium-high entropy alloy getter target is: V 40 Fe 27 Ti 30 Pr2Y1、V 40 Fe 20 Ti 20 Zr 10 Pr5Y5、V 40 Fe 15 Zr 30 Pr 7.5 Y 7.5 V 40 Pr 15 Y 15 Ti 15 Zr 15 V 40 Fe 27 Ti 30 Pr1Y1Er1、V 40 Fe 20 Ti 20 Zr 10 Pr4Y3Er3、V 40 Fe 15 Zr 30 Pr5Y5Er5、V 40 Pr10 Y 10 Er 10 Ti 15 Zr 15 V 40 Fe 27 Ti 30 Pr1Y1Er 0.5 Nd 0.5 V 40 Fe 27 Ti 30 Pr1Y 0.5 Er 0.5 Nd 0.5 Ce 0.5 V 40 Fe 27 Ti 30 Pr 0.5 Y 0.5 Er 0.5 Nd 0.5 Ce 0.5 Sm 0.5 V 40 Pr5Y5Er5Nd5Gd5Ce4Sm1Ti 15 Zr 15 .
[0016] A second aspect of the present invention provides a medium-high entropy alloy getter film, the getter film comprising the aforementioned medium-high entropy alloy getter target.
[0017] Preferably, the substrate film of the medium-high entropy alloy getter film includes silicon-based wafer substrate, stainless steel substrate and its film, titanium and titanium alloy substrate and its film, nickel and nickel alloy substrate and its film, zirconium and zirconium alloy substrate and its film, copper and copper alloy substrate and its film, aluminum and aluminum alloy substrate and its film, magnesium alloy substrate and its film, cobalt and cobalt alloy substrate and its film, iron-nickel-cobalt valved alloy substrate and its film, valved alloy substrate and its film, zirconia ceramic cover plate substrate, alumina ceramic cover plate, silicon carbide and inorganic non-metallic substrate.
[0018] The thickness of the medium-high entropy alloy gas-absorbing film substrate is 0.04~2 mm, and the thickness of the gas-absorbing film is 0.01~10 micrometers.
[0019] This invention also relates to a method for preparing a medium-high entropy alloy getter film, wherein a medium-high entropy alloy getter target is sputtered onto a substrate sample by a sputtering process to form a medium-high entropy alloy getter film. Preferably, the parameters of the sputtering process are set as follows: sputtering power 50-3500W, sputtering time 3-60min, sputtering temperature -50-150℃, argon gas is used for sputtering, and gas flow rate is 50-150 mL / min.
[0020] Preferably, the sputtering process comprises the following two-step process steps: S1: In the first sputtering step, the sputtering power is set to 3500W~2000W, the sputtering time is 3~5min, the sputtering temperature is -50-100℃, and the gas flow rate is 60-80 mL / min to form a low-density micron-scale defect structure. S2: In the second step, the sputtering power is adjusted to 2000W-500W, the sputtering time to 8-45min, the sputtering temperature to 20-150℃, and the gas flow rate to 80-150mL / min to form a high-density nanoscale defect structure and obtain a gradient structure multi-element alloy thin film getter.
[0021] The present invention has the following beneficial effects: This invention patent utilizes the advantages of medium-high entropy alloys, such as concentrated or multi-principal element alloys and high mixed entropy, to solve the serious contradiction between the gas-getting performance and mechanical properties (i.e., the bonding strength between the gas-getting film and the substrate) of current semiconductor MEMS sensor packaging materials. Due to the random interfusion of multiple elements, the non-periodic arrangement, and the complex potential field coupling effect of medium-high entropy alloys, they exhibit excellent physicochemical characteristics, specifically manifested in four major effects: a thermodynamic high-entropy effect, a structural lattice distortion effect, a kinetic hysteresis diffusion effect, and a property "cocktail" effect. In engineering applications, these four effects significantly improve the gas-getting performance and mechanical properties (i.e., the bonding strength between the gas-getting film and the substrate) of gas-getting materials. Attached Figure Description
[0022] Figure 1 This is a first flowchart of a medium-high entropy alloy gas-absorbing target provided in an embodiment of the present invention.
[0023] Figure 2 This is an XRD diagram of an embodiment of the present invention.
[0024] Figure 3 The instrument used in this invention is a D / MAX-2200 X-ray diffractometer.
[0025] Figure 4 This is a photograph of the constant pressure method testing instrument used in the research and development of this invention.
[0026] Figure 5 This is a photograph of the medium-high entropy alloy gas-absorbing film and the bonding strength testing instrument used in the research and development of this invention. Detailed Implementation
[0027] The terms “first,” “second,” “third,” “fourth,” etc. (if present) in the specification, claims, and accompanying drawings of this invention are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate so that the embodiments described herein can be implemented in orders other than those illustrated or described herein. Furthermore, the terms “comprising” or “having,” and any variations thereof, are intended to cover a non-exclusive inclusion; for example, a process, method, system, product, or apparatus that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or apparatus.
[0028] For medium-to-high entropy alloys, the mixing entropy is between 1.0R and 1.5R, and they are composed of 3-4 elements. Theoretically, the lattice distortion of medium-to-high entropy alloys distinguishes them from ordinary alloys in terms of structural characteristics. See Figure 1 , Figure 1 'a' represents a typical alloy crystal structure, where the atoms are in a stable equilibrium state. Looking at the direction of the arrow, the interatomic spacing is stable, and no torque or similar phenomena occur. Figure 1 b represents the crystal structure of a medium-to-high entropy alloy. Looking at the direction of the arrow, the lattice is distorted, the atoms are unstable, the interatomic spacing is unstable, and phenomena such as torque occur between atoms. Because the atomic equilibrium is disrupted, point defects such as midpoint defects, vacancies, interstitial atoms, and substitutional atoms increase. The gettering performance of the alloy increases with increasing defect concentration. This is because the increased defect concentration leads to an increase in the diffusion coefficients (Dx, Dy, Dz) of gas along the X, Y, and Z three-dimensional directions in the getter. The following formula shows the gas absorption capacity of the getter. That will increase.
[0029] Meanwhile, medium-high entropy alloys exhibit short-range chemical order and interactions with dislocations. Dislocations enhance the mechanical properties of the getter. Therefore, medium-high entropy alloys increase both the getter's getter capacity and its mechanical properties (the bonding strength between the getter film and the matrix), achieving a dual increase. See Figure 1 The potential energy in a medium-high entropy alloy system varies with the interatomic spacing.
[0030] For ease of understanding, the specific process of the embodiments of the present invention is described below. The first embodiment of the medium-high entropy alloy gas-getting target of the present invention includes: The medium-high entropy alloy getter target is composed of main element A, element C, and element B. The content of main element A is 25-40 at%, the content of element B is 30-45 at%, and the content of element C is 30-45 at %. The formula is: A25- 40 B 30-45 C 30-45 The main element A is selected from one or two of V and Co; the element C is selected from one or two of Fe and RE, where RE is one or more of Pr, Y, Gd, Nd, Er, Sm, and Ce; and the element B is selected from one or two of Ti and Zr.
[0031] The element C is selected from two of Fe and RE, and the RE content of element C is 3-15 at.
[0032] The composition of element C is as follows: Fe, Pr, Y; Fe, Pr, Gd; Fe, Pr, Nd; Fe, Pr, Er; Fe, Pr, Sm; Fe, Pr, Ce Fe, Pr, Y, Gd; Fe, Pr, Y, Nd; Fe, Pr, Y, Er; Fe, Pr, Y, Sm; Fe, Pr, Y, Ce; Fe, Pr, Y, Er; Fe, Pr, Y, Er, Sm; Fe, Pr, Y, Er, Ce; Fe, Pr, Y, Gd, Nd, Er, Sm, Ce; Pr, Y, Gd, Nd, Er, Sm, Ce.
[0033] In this invention, a new medium-entropy getter alloy is formed by adding 25-40 at% of a mandatory element B and 25-35 at% of an optional element C to a main element A of 30-40 at%. Component A consists of one or two of V and Co. Component B consists of one or two of Ti and Zr. Component C consists of one, two, or more of Fe, Pr, Y, Gd, Nd, Er, Sm, and Ce. The specific equation is as follows: (V 1-b Co b ) 30-40 (Ti 1-a Zr a ) 25-40 (Fe 1-x RE x (RE=Pr / Y / Gd / Nd / Er / Sm / Ce)) 25-35 (at%) Where: 0 ≤ a ≤ 1; 0 ≤ b ≤ 1; 0 ≤ x ≤ 1 at%. The formula is: A 25-40 B 25-40 C 25-30 Where B≠0. The preparation methods for medium-high entropy alloy getter targets and getter film samples are as follows: In the medium-to-high entropy alloy target material, the optional elements added are rare earth elements Pr, Y, Gd, Nd, Er, Sm, and Ce. Because rare earth elements are easily oxidized, they are added in the form of an intermediate alloy. The specific target material preparation is as follows: ① First, according to (V) 1-b Co b ) 25--40 (Ti 1-a Zr a ) 25-40 (Fe 1-x RE x (RE=Pr / Y / Gd / Nd / Er / Sm / Ce)) 25-30 (at%) where: 0 ≤ a ≤ 1; 0 ≤ b ≤ 1; 0 ≤ x ≤ 1 at% .
[0034] According to A 25-40 B 25-40 C 25-30 The formulation involves the formulation of a main element A, comprising one or both of V and Co, combined with one or both of the required element B (Ti and Zr) in a specific ratio, and then further combined with one or both of the optional element C (Fe, Pr, Y, Gd, Nd, Er, Sm, Ce) to form a multi-element alloy getter target and its getter film. The main element A has a content of 30-40 at%, the required element B has a content of 25-40 at%, and the ratio of the optional element B to the optional element C is 25-35 at%. The formulation equation is: A 25-40 B 25-40 C 25-30 Where B≠0.
[0035] ② Preparation method of intermediate alloy: To prevent the easy oxidation of rare earth elements during addition, it is prepared by a single anti-gravity melting process (V 40-b Co b)RE (40~80) (at%) (RE = Pr, Y, Gd, Nd, Er, Sm, Ce) master alloys are purified by secondary anti-gravity melting to achieve a purity of 99.99% and homogenization. For master alloys containing optional elements Pr, Y, Gd, Nd, Er, Sm, and Ce, 5% RE is added to prevent burn-off during melting and to maintain high purity. By combining anti-gravity melting and purification techniques, a high-purity 99.99% master alloy is prepared. The vacuum degree of the master alloy during melting is better than (1~5)×10⁻⁶. -3 Pa, melting temperature 1450~2420 ℃. Then cast, the cast intermediate alloy is broken into blocks of 2~10mm for later addition as needed in the alloy formulation.
[0036] ③ Prepare the intermediate alloy with a block size of 2-10mm according to its atomic percentage in the required A. 25-40 B 25- 40 C 25-30 In the alloy formulation (wherein the main element A includes one or both of V and Co, combined with one or both of the required element B, Ti and Zr, in a certain proportion, and then combined with one or two of the optional element C (Fe, Pr, Y, Gd, Nd, Er, Sm, Ce) to form a multi-element alloy getter target and its getter film. The content of the main element A is 30-40 at%, the content of the required element B is 25-40 at%, and the ratio of the optional element C to the optional element is 25-35 at%.), the specific molecular formula is as follows: ((V 1-b Co b)30-40 (Ti 1-a Zr a ) 25-40 (Fe 1-x RE x (RE=Pr / Y / Gd / Nd / Er / Sm / Ce)) 25-35 (at%) where: 0 ≤ a ≤ 1; 0 ≤ b ≤ 1; 0 ≤ x ≤ 1 (at%).
[0037] ④ Prepare alloy targets using consumable plasma melting technology. Plasma melting requires melting in an argon atmosphere at a temperature of 1450~2420 ℃, followed by casting in a water-cooled copper crucible (other casting methods are also possible), resulting in cylinders with a diameter of 30-350 mm. The cast gas-absorbing target cylinders are then heat-treated. The vacuum degree of the heat treatment is (1~5)×10⁻⁶. -3The heat treatment process, with temperatures ranging from 900 to 1200 °C and durations from 0.5 to 4 h, aims to achieve a relative density of 96%. For cylindrical samples with dimensions of 30-350 mm after heat treatment, hot isostatic pressing (HIP) is performed at a pressure of 200 MPa, a temperature of 1000-1500 °C, and a time of 0.5-3 h to achieve a relative density of 100%. The cylindrical samples, after HIP and with dimensions of 30-350 mm, are then machined and surface-ground to form discs with diameters of (25.4-330) × 6.5 mm, thus preparing 1-13 inch target materials. By melting indium (In), the medium-entropy getter alloy target material is bonded to a 6-7 mm thick copper plate to obtain 1-13 inch medium-high entropy alloy getter targets.
[0038] 2) Preparation of medium-to-high entropy alloy getter films: A getter film is prepared on a substrate using methods such as magnetron sputtering (PVD) or chemical vapor deposition (CVD). The types of substrate films include silicon-based wafer substrates, stainless steel substrates and their films, titanium and titanium alloy substrates and their films, nickel and nickel alloy substrates and their films, zirconium and zirconium alloy substrates and their films, copper and copper alloy substrates and their films, aluminum and aluminum alloy substrates and their films, magnesium alloy substrates and their films, cobalt and cobalt alloy substrates and their films, and various metal and alloy substrates and their films. The types of substrate films also include iron-nickel-cobalt valved alloy substrates and their films, as well as various valved alloy substrates and their films. The types of substrate films also include zirconia ceramic cover plates, alumina ceramic cover plates, and various ceramic cover plate substrates and their films. The getter film is formed on the surface of a silicon carbide or inorganic non-metallic substrate (without exclusion of any other material as a substrate). The substrate thickness is 0.04~2 mm, and the getter film thickness is 0.01~10 micrometers. The composition of the getter film is the same as that of the getter target material, which is (V 1-b Co b)30-40 (Ti 1-a Zr a ) 25-40 (Fe 1-x RE x (RE=Pr / Y / Gd / Nd / Er / Sm / Ce)) 25-35 (at%) where: 0 ≤ a ≤ 1; 0 ≤ b ≤ 1; 0 ≤ x ≤ 1 at% . That is, A 25-40 B 25-40 C 25-30The formulation involves the formulation of a main element A, comprising one or both of V and Co, combined with one or both of the required element B (Ti and Zr) in a specific ratio, and then further combined with one or both of the optional element C (Fe, Pr, Y, Gd, Nd, Er, Sm, Ce) to form a multi-element alloy getter target and its getter film. The main element A has a content of 30-40 at%, the required element B has a content of 25-40 at%, and the ratio of the optional element B to the optional element C is 25-35 at%. The formulation equation is: A 25-40 B 25-40 C 25-30 Where B≠0.
[0039] In an embodiment of the present invention, the content of main element A is 25 at%, 26 at%, 27 at%, 28 at%, 29 at%, 30 at%, 31 at%, 32 at%, 33 at%, 34 at%, 35 at%, 36 at%, 37 at%, 38 at%, 39 at%, and 40 at%; the content of element B is 30 at%, 31 at%, 32 at%, 33 at%, 34 at%, 35 at%, 36 at%, 37 at%, 38 at%, 39 at%, 40 at%, 41 at%, 42 at%, 43 at%, 44 at%, and 45 at%; and the content of element C is 30 at%, 31 at%, 32 at%, 33 at%, 34 at%, 35 at%, 36 at%, 37 at%, 38 at%, 39 at%, 40 at%, 41 at%, 42 at%, 43 at%, 44 at%, and 45 at%.
[0040] A method for preparing medium-high entropy alloy getter films involves sputtering a medium-high entropy alloy getter target onto a substrate sample to form a medium-high entropy alloy getter film. The parameters of the sputtering process are set as follows: sputtering power 30-3500W, sputtering time 3-60min, sputtering temperature -50-150℃, argon gas is used for sputtering, and gas flow rate is 50-150 mL / min.
[0041] The following are the three-step process steps: S1: Step 1, RF sputtering, sputtering power 30-1000W, time 3-10 minutes. The purpose is to create many defects to produce high-density defects for the second sputtering step.
[0042] S2: During the second sputtering step, the sputtering power is set to 3500W~2000W, the sputtering time is 3~5min, the sputtering temperature is -50-100℃, and the gas flow rate is 60-80 mL / min to form a low-density micron-scale defect structure. S3: In the third step, adjust the sputtering power to 2000W-500W, the sputtering time to 8-45min, the sputtering temperature to 20-150℃, and the gas flow rate to 80-150mL / min to form a high-density nanoscale defect structure and obtain a gradient structure multi-element alloy thin film getter.
[0043] 3) Testing of gas-absorbing thin films and bonding strength of medium- and high-entropy alloys (see Annex 1 and Annex 2 for details): The getter, prepared as a getter film, is subjected to a vacuum of 10... -4 After holding at 300–490 °C for 20–30 min under Pa conditions, the gas was cooled to room temperature, and the gas-absorbing performance at room temperature was tested. The test gases were hydrogen and carbon monoxide. The testing instrument is described in [link to instrument description]. Figure 3 The absorption rates of hydrogen and carbon monoxide at room temperature were 120–630 ml / s.cm, respectively. 2 41~390 ml / s.cm 2 The bonding strength between the getter film and the substrate film is 93~212 N. The specific surface area is 27~37 m2 / g.
[0044] Appendix 1: Specific Test Methods for Getter Membranes The method for testing the getter performance of samples 1-45 in Implementation Examples is as follows: According to the national standard GB / T 25497-2010 and ASTM F798-97 (2002) of the American Society for Testing and Materials, H2 and CO can be selected as the test gases for the getter performance of getter materials. Therefore, this application selects hydrogen and carbon monoxide as the test gases. The activation conditions for testing the getter film are: vacuum degree 10... -4 After holding at 300~490℃ for 20~30 min under Pa, the material was cooled to room temperature, and its gas-getting performance was tested at room temperature. All data in this invention were measured using the JE-L1-01 gas-getting performance testing system of Shanghai Jingwei Materials Technology Co., Ltd. (patent number for Jingwei materials testing device: control software for a constant pressure method testing instrument for gas-getting materials), see [link to relevant documentation]. Figure 2 .
[0045] In this embodiment of the invention, the JE-L1-01 constant pressure method getter performance testing system (patent number ZL202020109356.X) of Shanghai Jingwei Materials Technology Co., Ltd. is used for testing. This equipment conforms to the national standard GB / T 25497-2010 and the American Society for Testing and Materials (ASTM) F798-97(2002) standard. The specific testing steps are as follows: ① High vacuum: Place the sample to be tested into the sample chamber, and use a mechanical pump and a molecular pump to evacuate the constant pressure method getter system to a high vacuum of 10. -4 Below Pa; ② System baking and degassing: The pipeline is baked and degassed at a temperature of 200 ℃ for 13-16 h. The temperature of the sample is monitored in real time to ensure that it does not exceed 150 ℃, in order to prevent partial activation and oxidation of the sample. ③ Leakage rate: After baking and degassing, wait until the system cools to room temperature and the vacuum degree of the sample chamber is less than 1.0 × 10⁻⁶. - 4 Pa, close all valves, read the system pressure after 600 s, calculate the leakage rate, and proceed to the next step if it meets the requirements; otherwise, check the cause of the leak, repair it, and repeat the above steps. ④ Getter activation treatment: Open the valve and re-pump until the pressure drops to 1.0 × 10⁻⁶~ 4 Pa, then activate the sample with a high-frequency induction heater; ⑤ Inhalation performance test: Activation condition: at a vacuum degree of 10 -4 After activation by holding the system at 300-490℃ for 20-30 minutes under pressure, wait for the system to cool to room temperature (25℃), then introduce high-purity H2 (99.999%) and adjust pH. g And it remains constant at 4.0 × 10 -4 Record P (within the shortest possible time, less than 60 seconds). m The change of P over time t. (To ensure accuracy, the initial P...) m / P g ≥ 40 — ASTM getter test standard); ⑥ Sampling: After the test, inflate the system to take samples and evacuate it to a high vacuum. ⑦ Evaluate inhalation rate and inhalation volume: Calculate the inhalation rate and inhalation volume of the sample according to the formula.
[0046] Appendix 2: Test on the bonding strength between medium- and high-entropy alloy gas-getting films and substrates Regarding the alloy formulation techniques in Tables 1 and 2, in embodiments 1 to 45 of this patent, all samples were tested using a WS-2005 automatic coating adhesion scratch tester. See details... Figure 3 .
[0047] Table 1. (V) 1-b Co b ) 30-40 (Ti 1-a Zr a ) 25-40 (Fe 1-x RE x (RE=Pr / Y / Gd / Nd / Er / Sm / Ce)) 25-35 (at%) Implementation examples of getter films in medium-high entropy alloys (the alloy contains two or more groups of REs). Conclusion 1: With increasing RE content, both getter performance and matrix bonding strength increase. Optimal performance is achieved when RE content is between 3-15 at%. When RE content is <3% or >15%, both getter performance and matrix bonding strength decrease compared to samples with RE content between 3% and 15%. ③ Comparing samples 1 and 6, the addition of Pr significantly improves both getter performance and mechanical properties. Even with a specific surface area of 32 m², this improvement is not observed. 2 At / g, sample 4 showed significantly improved performance compared to sample 1, both in terms of air absorption and mechanical properties.
[0048] ④ Comparing Example 9 with Examples 2-5, it can be seen that in the alloy target and getter film where V and Co are both used as the main elements, the introduction of Co as the main element increases the strength between the film and the substrate. ⑤ Comparing Example 10 with Example 1, it can be seen that when Co completely replaces V, the performance is not very good, but it is better than Example 1 without the addition of RE primary color.
[0049] Conclusion 2 ① In the formula (V 1-b Co b ) 25 (Ti 1-a Zr a ) 40 (Fe 1-x Y x )) 35 In sample 14, Zr was in excess, completely replacing Ti. Samples 15-17 had excess Y, completely replacing Fe. ② With increasing RE content, gas absorption performance and matrix bonding strength increased. Performance was optimal when RE content was between 3-15 at%. ③ Comparing samples 1 and 12, the addition of Y significantly improved gas absorption performance and mechanical properties, even with a specific surface area of 32 m². 2 At / g, the performance of sample 12 is significantly improved compared to sample 1, both in terms of gas absorption and mechanical properties.
[0050] Conclusion 3 ① In the formula (V 1-b Cob)35 (Ti 1-a Zr a ) 35 (Fe 1-x Gd x )) 30 In sample 21, Zr was in excess, completely replacing Ti. In sample 22, Gd was in excess, completely replacing Fe. ② With increasing RE content, getter performance and matrix bonding strength increased. Performance was optimal when RE content was between 3-15 at%. ③ Comparing samples 1 and 13, the addition of Gd significantly improved getter performance and mechanical properties. Specifically, sample 19 had a 30m... 2 The surface area of sample 19 is lower than that of sample 1, and the performance of sample 19 is much better than that of sample 1, both in terms of air absorption and mechanical properties.
[0051] Conclusion 4 ① In the formula (V 1-b Co b)40 (Ti 1-a Zr a ) 35 (Fe 1-x Nd x )) 25 In sample 27, Zr was in excess, completely replacing Ti. In sample 28, Nd was in excess, completely replacing Fe. ② With increasing RE content, getter performance and matrix bonding strength increased. Performance was optimal when RE content was between 3-15 at%. ③ Comparing samples 1 and 25, the addition of Nd significantly improved getter performance and mechanical properties. Specifically, sample 25 had a 31m... 2 The surface area of sample 25 is lower than that of sample 1, while the performance of sample 25 is significantly improved compared to sample 1 in both gas absorption and mechanical properties. Sample 29 shows that excessive RE reduces its gas absorption performance and the bonding strength between the film and the matrix, due to the loss of solid solubility and defect characteristics of various elements in the high-entropy alloy. Sample 30 shows that the addition of elements outside the protected C element range, such as Yb, reduces its gas absorption performance and the bonding strength between the film and the matrix, because Yb has a 4f outer electron configuration. 14 5s 2 It is difficult to lose electrons, exhibiting the characteristics of Yb 2+ The characteristic of Yb is evident in the high-entropy alloys A25-40B30-45C30-45, where the C element exhibits a 3+ characteristic. 2+ The characteristics will cause the loss of elemental solid solubility and defect characteristics.
[0052] Conclusion 5 ① In the formula (V 1-b Co b)40 (Ti 1-a Zr a ) 35 (Fe1-x Er x )) 25 In sample 33, a was in excess, completely replacing Ti. In sample 34, Er was in excess, completely replacing Fe. ② With increasing RE content, getter performance and matrix bonding strength increased. Performance was optimal when RE content was between 3-15 at%. ③ Comparing samples 1 and 31, the addition of Er significantly improved both getter performance and mechanical properties. Even though sample 31 had a lower specific surface area than sample 1, both getter and mechanical properties were greatly improved.
[0053] Conclusion 6 ① In the formula (V 1-b Co b)40 (Ti 1-a Zr a ) 35 (Fe 1-x Nd x )) 30 In sample 37, Zr was in excess, completely replacing Ti. In sample 38, Sm was in excess, completely replacing Fe. ② With the increase of RE, the gas absorption performance and the bonding strength with the matrix increased. The performance was optimal when the RE content was between 3-15 at%. ③ Compared with sample 35, the addition of Sm significantly improved the gas absorption performance and mechanical properties. That is, sample 35 had a lower specific surface area than sample 1 (32), and the performance of sample 35 was much better than that of sample 1, both in terms of gas absorption and mechanical properties.
[0054] Conclusion 7 ① In the formula (V 1-b Co b)40 (Ti 1-a Zr a ) 30 (Fe 1-x Ce x )) 30 In sample 41, Zr was in excess, completely replacing Ti. In sample 42, Sm was in excess, completely replacing Fe. ② With increasing RE content, the gas absorption performance and matrix bonding strength increased. The performance was optimal when the RE content was between 3-15 at%. ③ Comparing samples 1 and 39, the addition of Sm significantly improved both gas absorption and mechanical properties. That is, sample 39 had a lower specific surface area than sample 1, but its performance, both in terms of gas absorption and mechanical properties, was significantly better than sample 1.
[0055] from Figure 2XRD analysis shows that the alloy targets in Examples 6, 18, and 23 all have a BCC (body-centered cubic) phase structure. This simple phase structure allows for easy control of the composition of the sputtered thin film during magnetron sputtering. The alloy compositions in Examples 6, 18, and 23 are: V40Fe15Zr30Pr15, Co25Ti20Zr10Y45, and V25Ti25Zr20Gd30, respectively, representing the compositions in Al... 25-40 B 30-45 C 30-45 The phase structure of high-entropy alloys within the range. It can be seen that, within the scope of the claims, the composition is in A... 25-40 B 30-45 C 30-45 The high-entropy alloys within the specified range are solid solutions, meaning the alloy target material consists of only one phase structure, namely the BCC structure. However, when an excess of RE elements is added, as in Example 29, the target alloy composition is V25Zr15Nd60, or when rare earth Yb other than RE (Pr, Y, Gd, Nd, Er, Sm, Ce) is added, as in Example 30, the target alloy composition is V40Fe15Zr30Yb15. As can be seen from the XRD diagram, Examples 29 and 30 have an additional FCC phase (face-centered cubic structure phase) on top of the original BCC phase, meaning that Examples 29 and 30 are composed of two phases.
[0056] Generally speaking, for magnetron sputtering, the ideal target structure is a solid solution phase, meaning one target corresponds to one phase structure. This is because each target, when working in the magnetron sputtering furnace, corresponds to only one sputtering power at any given time. It's impossible for one power source to correspond to two power levels simultaneously. Therefore, the target must be of a single phase. This ensures a uniform composition of the target sputtered onto the thin film. If the target has two components, it means that the technician must set the power to be adapted to only one of the two phases during sputtering, and the target will selectively sputter during operation. This will cause changes in the composition transferred from the target to the thin film (adapting only to BCC or only to FCC, since BCC and FCC have different compositions and cell structures), resulting in a significant deviation between the thin film composition and the target composition. Due to this compositional deviation, the getter performance or mechanical properties will decrease, meaning the getter performance and mechanical properties of the thin film cannot be reliably controlled.
[0057] The experiments in this paper used a D / MAX-2200 X-ray diffractometer (Figure 3), with a Cu target as the Kα ray, a wavelength of λ = 1.5406 Å, and a scanning angle range of 20~90˚.
[0058] Table 2. (V) 1-b Co b ) 25-40 (Ti1-a Zr a ) 25-40 (Fe 1-x RE x (RE=Pr / Y / Gd / Nd / Er / Sm / Ce)) 25-40 Implementation examples of getter films in (at%) medium-high entropy alloys (the alloy contains two or more groups of REs).
[0059] Conclusion 9: ① In the formula (V 1-b Co b)40 (Ti 1-a Zr a ) 30 (Fe 1-x RE x )) 30 In the formula (RE=Pr / Y), samples 43-46 contained a mixture of Pr and Y elements from RE. Sample 46 had an excess of RE, completely replacing Fe. ② As the content and type of rare earth element RE increased, the gas absorption performance and matrix bonding strength increased. The performance was optimal when the RE content was between 3-15 at%. ③ Comparing samples 43 and 2, the addition of both rare earth elements RE significantly improved both gas absorption and matrix bonding performance (mechanical properties).
[0060] Conclusion 10: ① In the formula (V 1-b Co b)40 (Ti 1-a Zr a ) 30 (Fe 1-x RE x )) 30( In the formula RE = Pr / Y / Er, samples 47-50 contain a mixture of Pr, Y, and Er from RE. Sample 50 has an excess of RE, which completely substitutes for Fe.
[0061] ② As the content and types of rare earth elements (RE) increase, the gas absorption performance and the bonding strength with the matrix increase. The performance is optimal when the RE content is between 3-15 at%.
[0062] ③ Comparing samples 47 and 2, the addition of the three rare earth elements (RE) significantly improves both gas absorption and matrix bonding (mechanical properties).
[0063] Conclusion 11: ① In the formula (V1-b Co b)40 (Ti 1-a Zr a ) 30 (Fe 1-x RE x )) 30( In the formula RE = Pr / Y / Gd / Nd / Er / Sm / Ce, samples 51-54 represent the combined addition of four, five, six, and seven elements of RE, respectively. Sample 54 has an excess of RE, completely replacing Fe.
[0064] ② As the content and types of rare earth elements (RE) increase, the gas absorption performance and the bonding strength with the matrix increase. The performance is optimal when the RE content is between 3-15 at%.
[0065] ③ Comparing samples 51-54, the combined addition of seven elements in RE resulted in better getter and mechanical properties than the combined addition of six elements; similarly, the combined addition of six elements in RE resulted in better getter and mechanical properties than the combined addition of five elements; the combined addition of five elements in RE resulted in better getter and mechanical properties than the combined addition of four elements; and the combined addition of four elements in RE resulted in better getter and mechanical properties than the combined addition of three and two elements. The more elements in RE, the better the getter and mechanical properties. Both getter and mechanical properties are significantly improved. This is because the more elements added, the greater the entropy change of the alloy based on the original alloy formula. Figure 1 The potential energy in the medium-high entropy alloy system changes with the interatomic spacing, indicating that the interatomic spacing is unstable, resulting in phenomena such as torque, and the unbalanced energy of the system increases. Because the atomic equilibrium state is disrupted, defects such as midpoint defects, vacancy defects, interstitial atoms, and substitutional atoms increase in the medium-high entropy alloy. The gas absorption performance of the alloy increases with the increase of defect concentration. Because the defect concentration increases, the diffusion coefficient (Dx, Dy, Dz) of the gas in the getter along the three-dimensional X, Y, and Z directions increases. It can be seen from formula (1) that the gas absorption capacity of the thin film getter is... This increases the getter's mechanical properties. Simultaneously, the medium-to-high entropy alloy exhibits short-range chemical order and interactions with dislocations, which enhance the mechanical properties of the thin-film getter. Thus, the thin-film getter achieves a dual increase in both getter performance and mechanical properties (bonding strength with the matrix).
[0066] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A medium-high entropy alloy getter target, characterized in that, The medium-high entropy alloy is used to prepare a medium-high entropy alloy gas-absorbing film, and the medium-high entropy alloy has a single-phase structure. The medium-high entropy alloy getter target is composed of main element A, element C, and element B. The content of main element A is 25-40 at%, the content of element B is 30-45 at%, and the content of element C is 30-45 at %. The formula is: A 25- 40 B 30-45 C 30-45 ; The main element A is selected from one or both of V and Co; The element B is selected from one or both of Ti and Zr; The element C is Fe and RE, and the RE content in the medium-high entropy alloy is 3-15 at%, RE is one or more of Pr, Y, Gd, Nd, Er, Sm and Ce.
2. The medium-high entropy alloy gas-getting target material according to claim 1, characterized in that, The formula equation of the medium-high entropy alloy gettering target material is: V 40 Fe 27 Ti 30 Pr3, V 40 Fe 20 Ti 20 Zr 10 Pr 10 , V 40 Fe 15 Zr 30 Pr 15 , V 25 Fe 32 Ti 40 Y3, V 25 Fe 20 Ti 20 Zr 20 Y 15 , V 25 Fe 20 Zr 40 Y 15 , V 35 Fe 27 Ti 35 Gd3, V 35 Fe 20 Ti 20 Zr 15 Gd 10 , V 35 Fe 15 Zr 35 Gd 15 , V 40 Fe 27 Ti 30 Nd3, V 40 Fe 20 Ti 20 Zr 10 Nd 10 , V 40 Fe 15 Zr 30 Nd 15 , V 40 Fe 27 Ti 30 Sm3, V 40 Fe 20 Ti 20 Zr 10 Sm 10 , V 40 Fe 15 Zr 30 Sm 15 , V 40 Fe 27 Ti 30 Ce3, V 40 Fe 20 You 20 Zr 10 If 10 、In 40 Fe 15 Zr 30 If 15 。 3. The medium-high entropy alloy gas-getting target material according to claim 1, characterized in that, The formulation equation for the medium-high entropy alloy gas-getting target is: V 40 Fe 27 Ti 30 Pr2Y1、V 40 Fe 20 Ti 20 Zr 10 Pr5Y5、V 40 Fe 15 Zr 30 Pr 7.5 Y 7.5 V 40 Fe 27 Ti 30 Pr1Y1Er1、V 40 Fe 20 Ti 20 Zr 10 Pr4Y3Er3、V 40 Fe 15 Zr 30 Pr5Y5Er5、V 40 Fe 27 Ti 30 Pr1Y1Er 0.5 Nd 0.5 V 40 Fe 27 Ti 30 Pr1Y 0.5 Er 0.5 Nd 0.5 Ce 0.5 V 40 Fe 27 Ti 30 Pr 0.5 Y 0.5 Er 0.5 Nd 0.5 Ce 0.5 Sm 0.5 .
4. A medium-high entropy alloy getter film, characterized in that, The gas-absorbing film includes the medium-high entropy alloy gas-absorbing target material as described in claim 1.
5. The medium-high entropy alloy getter film according to claim 4, characterized in that, The thickness of the medium-high entropy alloy gas-absorbing film substrate is 0.04~2 mm, and the thickness of the gas-absorbing film is 0.01~10 micrometers.
6. A method for preparing a medium-high entropy alloy getter film as described in claim 4, characterized in that, Medium- and high-entropy alloy getter targets are sputtered onto a substrate sample to form a medium- and high-entropy alloy getter film. The parameters of the sputtering process are set as follows: sputtering power 30-3500W, sputtering time 3-60min, sputtering temperature -50-150℃, argon gas is used for sputtering, and gas flow rate is 50-150 mL / min.
7. A method for preparing a medium-high entropy alloy getter film as described in claim 6, characterized in that, The sputtering process consists of the following three steps: S1: Step 1, radio frequency sputtering, sputtering power 30-1000W, time 3-10min; S2: During the second sputtering step, the sputtering power is set to 3500W~2000W, the sputtering time is 3~5min, the sputtering temperature is -50-100℃, and the gas flow rate is 60-80 mL / min to form a low-density micron-scale defect structure. S3: In the third step, adjust the sputtering power to 2000W-500W, the sputtering time to 8-45min, the sputtering temperature to 20-150℃, and the gas flow rate to 80-150mL / min to form a high-density nanoscale defect structure and obtain a gradient structure multi-element alloy thin film getter.
Citation Information
Patent Citations
Gas adsorption alloy material and application thereof
CN108149069A
Hydrogen purification and small-flow control device in getter measurement system
CN211553936U
High-performance Ti-Co-RE target material and method for preparing high-getter-capacity film getter
CN112626460A
Method of storing hydrogen
US4111689A